1905 Minn. Gen. Laws 620, ch. 344, § 53. - (:unkn) unknown (General Publisher, 1905)
No person shall have in his possession within any such park or within one-half mile of the outer limits thereof, any gun, revolver, or other firearm unless the same is unloaded, and except after the same has been sealed by the park commissioner or a deputy appointed by him, and except such gun or other firearm at all times during which it may be lawfully had in such park remains so sealed and unloaded.
--
Keywords: SENSITIVE PLACES